Public vows : a history of marriage and the nation / by Nancy F. Cott. - Cott, Nancy F. (Harvard University Press, 2002)
This volume examines the political history of marriage, analysing the shaping of the accepted model of consensual, lifelong monogamy by legislators and judges throughout American history.